State of the Art of Therapeutic Endocrinology - Magdeldin, Sameh (IntechOpen, 2012)
During the last two decades, evidence of increasing trends of several endocrine-related disorders has been strengthened. These disorders often come with lack of uniform diagnosis and/ or even unclear endocrine disruption. The later is mainly due to abnormal classical changes in the blood- released hormone to its targeted organ, abnormal communication between cells within a tissue or organ (paracrine), within the same cell (intracrine) or signals which act on the same cell (autocrine). This challenging status drives endocrinologists to the urgent need to address enormous knowledge gaps in this wide field of research (Endocrinology). From the perspective point of view that "hormones control our bodies", we need to get these hormones rebalanced so we can restore overall health. That is simply endocrinology!